Switching from IFX originator to biosimilar CT-P13 does not impact effectiveness, safety and immunogenicity in a large cohort of IBD patients. (2nd January 2021) - Pugliese, Daniela; Guidi, Luisa; Privitera, Giuseppe; Bertani, Lorenzo; Tolusso, Barbara; Papparella, Luigi Giovanni; Maltinti, Simona; Di Mario, Clara; Onali, Sara; Ceccarelli, Linda; Rapaccini, Gian Lodovico; Scaldaferri, Franco; et al.
ABSTRACT: Background: Switching from IFX originator to CT-P13 is safe; however, little data on immunogenicity exists. Research design and methods: Consecutive IBD patients on IFX originator were switched to CT-P13 and followed-up for 12 months. Clinical activity, infliximab trough levels (ITLs), anti-drug antibodies (ATIs), and adverse events were recorded at predefined timepoints (baseline, second CT-P13 infusion, 6 and 12 months). The outcomes investigated were immunogenicity, pharmacokinetics, effectiveness and safety. Results: 119 patients were switched to CT-P13 after a median time with IFX of 5.8 years. No changes in mean ITLs were observed. ATIs were detected in 30 patients (25.2%): 14 before and 16 after switch. Mean persistent ATIs were significantly higher compared to mean transient ones (109.74 ng/mL ±84.70 vs 18.22 ng/mL ±11.37, p < 0.001), with significantly lower ITLs associated (mean 0.32 µg/mL ±0.6 vs 3.08 µg/mL ±3.22, p < 0.001). A significant decrease of patients in steroid-fee clinical remission was observed after the switch (p = 0.004), with subsequent improvement at 6 months (p = 0.005). Eighteen patients (15.1%) discontinued IFX, only 6 (5%) for loss of response. Conclusions: Switching from infliximab originator to CT-P13 seems safe and effective, without differences in immunogenicity. A temporary reduction of clinical benefit after switching could be potentially explained by a 'nocebo-effect response'.